Thinking Outside the Girl Box : Teaming Up with Resilient Youth in Appalachia - Spatig, Linda, 1948-; Amerikaner, Layne, 1986- (Book collections on Project MUSE., 2014)
"Thinking outside the girl box is a true story about a remarkable youth development program in rural West Virginia. Based on years of research with adolescent girls -- and adults who devoted their lives to working with them -- Thinking Outside the Girl Box reveals what is possible when young people are challenged to build on their strengths, speak and be heard, and engage critically with their world. Based on twelve years of field research, the book traces the life of the Lincoln County Girls' Resiliency Program (GRP), a grassroots, community nonprofit aimed at helping girls identify strengths, become active decision makers, and advocate for social change. In the late 1990s and early 2000s, the GRP flourished. Its accomplishments were remarkable: girls recorded their own CDs, published poetry, conducted action research, opened a coffeehouse, performed an original play, and held political rallies at West Virginia's State Capitol. The organization won national awards, and funding flowed in. Today, in 2013, the programming and organization are virtually nonexistent. Thinking Outside the Girl Box raises pointed questions about how to define effectiveness and success in community-based programs and provides practical insights for anyone working with youth. Written in an accessible, engaging style and drawing on collaborative ethnographic research that the girls themselves helped conduct, the book tells the story of an innovative program determined to challenge the small, disempowering "boxes" girls and women are so often expected to live in"--Provided by publisher